Kerangka Dasar Pemikiran Pendidikan Naquib Al-Attas: Rekonstruksi Konseptual dalam Filsafat Pendidikan - Rawanita, Mesi; Walidin, Warul (STAI Muhammadiyah Paciran Lamongan, 2025)
This article analyzes the foundational framework of Syed Muhammad Naquib Al-Attas's educational thought as a critical response to contemporary Islamic education's epistemological and moral crises. Al-Attas highlights the centrality of ta’dib as the essence of Islamic education, encompassing the internalization of Islamic values and ethics to shape individuals with adab and wisdom. His concept of the Islamization of knowledge serves as a strategic approach to filter Western secular influences in educational paradigms. This study employs a qualitative-conceptual approach through literature analysis of Al-Attas’s major works. The findings reveal that Al-Attas's thought is highly relevant for reconstructing a holistic, value-oriented, and spiritually grounded Islamic education system. This article contributes to developing an authentic and contextual philosophy of Islamic education amid the challenges of globalization.